Seismic behaviour of reinforced concrete structure with vertical steel shear link - Hosseini, Seyed Hamed (2020)
Steel cross bracing system is a simple, economical and effective method of resisting lateral loadings for multi-story buildings. Vertical Shear Link (VSL), known as steel shear panel, is an efficient passive control system suitable for construction resistance against earthquakes. VSL has been installed between the joints of invert V-brace and reinforced concrete beams. VSL absorbs earthquake energy through the yielding of steel, while other structure’s members stay in an elastic condition. Limited numerical studies have been conducted on VSL applied to Reinforced Concrete (RC) building frames with eccentric steel bracing. Furthermore, studies seeking to identify performance level and the seismic response of RC structures using VSL and plastic hinge formations are also limited. A study of ductility and stiffness of RC frames with/without VSL is required. Therefore, a lateral load transfer mechanism, from RC frame to VSL, needs to be investigated. The aim of this research is to conduct a numerical study, verification and parametric investigation through time history and pushover analyses. The experimental intention is to study the stiffness, ductility and energy absorption of RC frame using VSL. This system has the ability to control the stiffness and ductility of a structure; while both are important structural seismic characteristics. The experimental study is conducted on a conventional RC frame in comparison with a VSL retrofitting system. The experimental findings are used to validate Finite Element Analysis (FEA) models using ABAQUS software. Further parametric studies are developed to evaluate the effect of VSL shear capacity. Two categories of RC frame i.e., low-level and mid-level, are analysed using SAP 2000 structural analysis software. Two types of analysis are considered i.e., nonlinear static (pushover) and nonlinear time history. The parameters considered are invert V-brace and RC structure with VSL. FEA results show that the frame with the VSL system increased shear force capacity to 170% compared to the conventional RC frame. Meanwhile, invert V-brace increased the shear force capacity of the frame to approximately 200%. The ductility of the RC frame reduced to 160% due to buckling of the invert V-brace, while the RC frame with VSL satisfied the ductility. Observations from the experimental test show that VSL worked correctly inside the RC frame. The VSL system could properly absorb the imported lateral force to the RC frame; where the shear yielding mechanism of the VSL could prevent buckling of the braces. The VSL system, as a proposed alternative method to construct ductile structures, is clarified with great lateral stiffness. Moreover, the axial forces developed in the braces can be controlled by the VSL system.